HAK ATAS UPAH SELAMA PEMUTUSAN HUBUNGAN KERJA (STUDI KASUS: PUTUSAN PENGADILAN NEGERI TANJUNG PINANG NOMOR 26/PDT.SUS-PHI/2019/PN TPG) - Diana Deborah; Gunardi Lie (Fakultas Hukum Universitas Tarumanagara, 2021)
Termination of employment is one of the problems that often occurs in the working relationship between workers/employees and employers. The termination of an employment relationship is a very complex problem due to the worker/employees losing their livelihood. One aspect of the cause of the termination of the employment relationship is because the worker made a serious mistake and if the termination of employment is inevitable, they must follow Indonesian Labour Law Act 13 of 2003. The employers often take unilateral actions, by giving the warning letter and the consequences of termination of employment without asking for clarification from the workers who are involved. So in the event of termination of employment, many workers don’t get the rights according to the law. This research is normative with library research data collection techniques. Like a scale that is used as a symbol of justice, the judges must also weigh in order to fulfill the workers property rights, so that in this case the workers rights can be fulfilled.